Defective titanium-based metal organic framework material, preparation method and application thereof, method for photocatalytic degradation of formaldehyde and coating compound
By introducing acetic acid into TiO2@NH2-MIL-125 and using non-thermal plasma-assisted synthesis technology, defective titanium-based metal organic framework materials were synthesized, solving the problem of low formaldehyde degradation efficiency of existing photocatalysts, achieving efficient photocatalytic degradation effect, and the material is environmentally friendly.
Patent Information
- Application Number
- CN202411958608.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
Existing photocatalysts are inefficient in degrading formaldehyde, and are prone to inactivation or structural damage during long-term operation, which cannot meet the requirements of practical applications.
By introducing acetic acid as a preparation in TiO2@NH2-MIL-125 and using non-thermal plasma-assisted synthesis technology, a defective titanium-based metal organic framework material (TiO2@NMX) with a ligand structure was synthesized. This material forms more structural defects and oxygen vacancies through plasma treatment, promoting efficient separation of electron-holes and improving photocatalytic reaction efficiency.
The efficiency of photocatalytic degradation of formaldehyde is improved, especially under visible light, and the material is environmentally friendly and has no secondary pollution.
Smart Images

Figure CN119775580A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of harmful gas pollution control, and in particular to a defective titanium-based metal organic framework material, a preparation method and application thereof, a method for photocatalytically degrading formaldehyde, and a coating composite. Background Art
[0002] Nowadays, a large amount of volatile organic compounds released by indoor building materials can deteriorate indoor air quality. Among these volatile organic compounds, formaldehyde is widely present in the indoor environment and can have toxic effects on the human body, such as nasal tumors and skin allergies. Therefore, the development of effective technologies to ensure high indoor air quality is regarded as a top priority. At present, a variety of technologies have been developed to eliminate indoor formaldehyde, including ventilation, adsorption, catalytic oxidation and thermal catalysis. Among the above technologies, photocatalytic oxidation of formaldehyde is one of the most promising environmentally friendly methods. It has been proved that photocatalytic oxidation of formaldehyde is also an effective method for removing indoor formaldehyde. To date, many metal oxides or metal organic framework materials, such as TiO2, BiVO4 and NH2-MIL-125, have been synthesized and applied in the field of air purification. However, these photocatalysts still cannot meet the requirements of practical applications due to high charge carrier recombination rate, narrow light absorption range, slow surface reaction, low efficiency and poor stability. At the same time, for typical catalysts under working conditions, the adsorption and reaction of gas molecules on the catalyst surface are limited by mass transfer processes. At the same time, they are easily filled with water or oxygen in the air, or blocked by intermediate products, which may cause the photocatalyst to be deactivated or structurally damaged during long-term operation. Therefore, it is necessary to optimize the pore structure of the catalyst and improve the adsorption capacity of gas molecules, thereby improving the mass transfer efficiency.
[0003] Among various MOFs, NH2-MIL-125 has a large specific surface area, abundant active functional groups, multiple active adsorption sites and efficient electron transfer capacity. However, when NH2-MIL-125 is used as a photocatalyst for photocatalytic degradation of formaldehyde, it has the problem of low photocatalytic degradation efficiency. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a defective titanium-based metal organic framework material and its preparation method and application, a method for photocatalytic degradation of formaldehyde and a coating composite. The defective titanium-based metal organic framework material obtained by the preparation method provided by the present invention has high photocatalytic degradation activity, especially high photocatalytic degradation activity for formaldehyde.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a defective titanium-based metal organic framework material, comprising the following steps:
[0007] In an organic solvent, titanium dioxide, 2-aminoterephthalic acid, acetic acid and an organic titanium source are sequentially added to obtain a reaction raw material liquid;
[0008] The reaction raw material liquid is reacted to obtain a precursor;
[0009] The precursor is subjected to plasma treatment to obtain the defective titanium-based metal organic framework material.
[0010] Preferably, the mass of the acetic acid is 30 to 150% of the mass of 2-aminoterephthalic acid.
[0011] Preferably, the dosage ratio of the 2-aminoterephthalic acid and the organic titanium source is 0.8-1.2:0.45-0.52 g / mL;
[0012] The mass ratio of the titanium dioxide to the organic titanium source is 0.1:1 to 0.2:1, and the particle size of the titanium dioxide is 20 to 25 nm;
[0013] The organic titanium source includes tetraisopropyl titanate.
[0014] Preferably, the reaction temperature is 120-160° C. and the reaction time is 20-26 hours.
[0015] Preferably, after the reaction, the method further comprises: centrifuging the obtained reaction liquid, and sequentially washing, purifying and vacuum activating the obtained solid to obtain a precursor;
[0016] The centrifugal separation is performed at a speed of 8000 to 10000 rpm for 5 to 10 minutes;
[0017] The washing comprises sequentially performing N,N-dimethylformamide washing and methanol washing; the number of N,N-dimethylformamide washing is ≥3 times, and the number of methanol washing is ≥3 times;
[0018] The purification reagent includes ethanol and acetic acid, the volume ratio of ethanol to acetic acid is 9:1, the purification temperature is 80-90°C, and the time is 5-7h;
[0019] The vacuum degree of the vacuum activation is 0.05MPa-0.09MPa, the temperature is 120-150°C, and the time is 10-24h.
[0020] Preferably, the plasma treatment is argon plasma treatment, and the pressure of the argon plasma treatment is 20 Pa, the power is 100-300 W, and the time is 40-120 min.
[0021] The present invention also provides a defective titanium-based metal organic framework material prepared by the preparation method described in the above technical solution.
[0022] The present invention also provides the use of the defective titanium-based metal organic framework material described in the above technical solution in photocatalytic degradation of formaldehyde.
[0023] The present invention also provides a method for photocatalytic degradation of formaldehyde, comprising the following steps:
[0024] The catalyst is brought into contact with the formaldehyde-containing gas, and the formaldehyde is degraded under light conditions;
[0025] The catalyst is the defective titanium-based metal organic framework material described in the above technical solution.
[0026] The present invention also provides a coating composite, comprising a substrate and a coating coated on the substrate, wherein the raw materials for preparing the coating include resin and filler, and the filler is the defective titanium-based metal organic framework material described in the above technical solution.
[0027] The invention provides a method for preparing a defective titanium-based metal organic framework material.
[0028] In the preparation process of the present invention, acetic acid is introduced as a modulator in TiO2@NH2-MIL-125, and non-thermal plasma-assisted synthesis technology is used to synthesize a defective titanium-based metal organic framework material (TiO2@NMX) with a ligand structure. In the preparation process, with the increase of acetic acid content and the auxiliary modification of plasma, the ligands in the precursor are continuously decarboxylated, the Ti-O clusters increase, and more structural defects are formed; at the same time, the precursor band gap decreases, and more oxygen vacancies are generated; the introduction of more structural defects and oxygen vacancies can promote efficient separation of electrons and holes, thereby promoting the efficiency of photocatalytic reactions under visible light. In summary, the defective titanium-based metal organic framework material (TiO2@NMX) prepared by the present invention can provide more active sites and channels, increase its contact area with HCHO molecules, and thus improve mass transfer efficiency. In addition, the defective titanium-based metal organic framework material can also utilize the rich active sites of the metal organic framework, show strong photocatalytic activity, and realize self-photodegradation of formaldehyde under visible light. The present invention provides a new way to obtain defective structure MOFs and improve photocatalytic performance. In addition, the defective titanium-based metal organic framework material obtained by the present invention is environmentally friendly and has no secondary pollution. The preparation method of the present invention has a simple process flow, strong operability, and broad practical application prospects.
[0029] The data of the examples show that the degradation efficiency of the defective titanium-based metal organic framework material of the present invention for photocatalytic degradation of formaldehyde for 120 min is 64.76-95.27%.
[0030] The present invention also provides a method for photocatalytic degradation of formaldehyde, comprising the following steps: contacting a catalyst with a formaldehyde-containing gas, and performing formaldehyde degradation under light conditions; the catalyst is the defective titanium-based metal organic framework material described in the above technical solution. The photocatalytic degradation method of the present invention has a high formaldehyde degradation rate and is easy to operate.
[0031] The present invention also provides a coating composite, comprising a substrate and a coating coated on the substrate, wherein the raw materials for preparing the coating include resin and filler, and the filler is the defective titanium-based metal organic framework material described in the above technical solution. The coating composite of the present invention can degrade harmful gas formaldehyde and can also substantially improve the inherent properties of the substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The X-ray crystal diffraction patterns of the materials obtained in the examples and comparative examples are as follows;
[0033] Figure 2 Scanning electron microscope photographs of NH2-MIL-125 (a) obtained in Comparative Example 3, TiO2@NM (b) obtained in Comparative Example 2, TiO2@NM4 (c) obtained in Example 4, and TiO2@NM5 (d) obtained in Example 5;
[0034] Figure 3 The photocatalytic degradation curves of the materials obtained in the examples and comparative examples under visible light;
[0035] Figure 4 The degradation efficiency of the materials obtained in the examples and comparative examples for photocatalytic degradation of formaldehyde for 120 min;
[0036] Figure 5 This is the experimental effect diagram of cyclic photocatalytic degradation of formaldehyde by TiO2@NM4 obtained in Example 4. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing a defective titanium-based metal organic framework material, comprising the following steps:
[0038] In an organic solvent, titanium dioxide, 2-aminoterephthalic acid, acetic acid and an organic titanium source are sequentially added to obtain a reaction raw material liquid;
[0039] The reaction raw material liquid is reacted to obtain a precursor;
[0040] The precursor is subjected to plasma treatment to obtain the defective titanium-based metal organic framework material.
[0041] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0042] The invention sequentially adds titanium dioxide, 2-aminoterephthalic acid, acetic acid and an organic titanium source into an organic solvent to obtain a reaction raw material liquid.
[0043] In the present invention, the particle size of the titanium dioxide is preferably 20 to 25 nm. In the present invention, the organic solvent preferably includes N,N-dimethylformamide and methanol, and the volume ratio of N,N-dimethylformamide to methanol is preferably 9:1. In the present invention, the organic titanium source preferably includes tetraisopropyl titanate.
[0044] In the present invention, the mass of the acetic acid is preferably 30-150% of the mass of 2-aminoterephthalic acid, specifically 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140% or 150%.
[0045] In the present invention, the usage ratio of the 2-aminoterephthalic acid and the organic titanium source is preferably 0.8-1.2:0.45-0.52 g / mL, specifically 1.087:0.52 g / mL.
[0046] In the present invention, the mass ratio of the titanium dioxide to the organic titanium source is preferably 0.1:1 to 0.2:1, specifically 0.1:1, 0.15:1 or 0.2:1.
[0047] In the present invention, the titanium dioxide is preferably ultrasonically dispersed after being added.
[0048] In the present invention, the acetic acid is preferably added dropwise.
[0049] The present invention introduces acetic acid as a modulator, which can adjust the electronic and morphological structure of MOF (TiO2@NH2-MIL-125), thereby effectively improving the oxidizability of defective titanium-based metal organic framework materials and increasing active sites, thereby improving the photocatalytic degradation activity of defective titanium-based metal organic framework materials.
[0050] After obtaining the reaction raw material liquid, the present invention reacts the reaction raw material liquid to obtain a precursor.
[0051] In the present invention, the reaction temperature is preferably 120-160°C, specifically preferably 120°C, 130°C, 140°C, 150°C or 160°C; the reaction time is preferably 20-26h, specifically 20h, 21h, 22h, 23h, 24h, 25h or 26h.
[0052] In the present invention, the reaction is preferably carried out in a Teflon-lined stainless steel autoclave.
[0053] After the reaction, the present invention preferably further comprises: centrifuging the obtained reaction liquid, and sequentially washing, purifying and vacuum activating the obtained solid to obtain a precursor.
[0054] In the present invention, the rotation speed of the centrifugal separation is preferably 8000-10000 rpm, specifically 8000 rpm, 8500 rpm, 9000 rpm, 9500 rpm or 10000 rpm; the time is preferably 5-10 min, specifically 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.
[0055] In the present invention, the washing preferably includes sequentially performing N,N-dimethylformamide washing and methanol washing; the number of N,N-dimethylformamide washing is preferably ≥3 times, specifically preferably 3 times; the number of methanol washing is preferably ≥3 times, specifically preferably 3 times.
[0056] In the present invention, the purification reagent preferably includes ethanol and acetic acid, and the volume ratio of ethanol to acetic acid is preferably 9: 1. In the present invention, the purification temperature is preferably 80-90°C, specifically 80°C, 85°C or 90°C; the time is preferably 5-7h, specifically 5h, 6h or 7h.
[0057] In the present invention, the vacuum degree of the vacuum activation is preferably 0.05MPa to 0.09MPa, specifically 0.05MPa, 0.06MPa, 0.07MPa, 0.08MPa or 0.09MPa; the temperature is preferably 120 to 150°C, specifically 120°C, 130°C, 140°C or 150°C; the time is preferably 10 to 24h, specifically 10h, 12h, 15h, 18h, 20h, 21h, 22h, 23h or 24h. In the present invention, the vacuum activation is preferably carried out in a vacuum drying oven.
[0058] After obtaining the precursor, the present invention performs plasma treatment on the precursor to obtain the defective titanium-based metal organic framework material.
[0059] In the present invention, the plasma treatment is preferably argon plasma treatment, the pressure of the argon plasma treatment is preferably 20 Pa, the power is preferably 100-300 W, specifically 100 W, 150 W, 200 W, 250 W or 300 W; the time is preferably 40-120 min, specifically 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.
[0060] In the present invention, during the plasma treatment process, the ligands in the precursor are continuously decarboxylated, resulting in an increase in Ti-O clusters and the formation of more defects; at the same time, the band gap of the precursor is reduced, resulting in more oxygen vacancies; more defects and oxygen vacancies can promote efficient electron-hole separation, and ultimately improve the photocatalytic degradation activity of defective titanium-based metal-organic framework materials.
[0061] The present invention also provides a defective titanium-based metal organic framework material prepared by the preparation method described in the above technical solution.
[0062] The present invention also provides the use of the defective titanium-based metal organic framework material described in the above technical solution in photocatalytic degradation of formaldehyde. The present invention does not specifically limit the application of the defective titanium-based metal organic framework material, and the operation familiar to those skilled in the art can be used.
[0063] The present invention also provides a method for photocatalytic degradation of formaldehyde, comprising the following steps:
[0064] The catalyst is brought into contact with the formaldehyde-containing gas, and the formaldehyde is degraded under light conditions;
[0065] The catalyst is the defective titanium-based metal organic framework material described in the above technical solution.
[0066] The present invention does not specifically limit the content of formaldehyde in the formaldehyde-containing gas, and those skilled in the art may set it according to actual needs.
[0067] The present invention does not specifically limit the amount of the catalyst, and those skilled in the art can set it according to actual needs.
[0068] In the present invention, the light source of the illumination is preferably a xenon lamp light source, the wavelength of the xenon lamp light source is preferably 200nm to 780nm, and the power of the xenon lamp light source is preferably 300W. In the present invention, the temperature of the formaldehyde degradation is preferably 30 to 35°C. The present invention does not specifically limit the time of the formaldehyde degradation, as long as the formaldehyde can be fully degraded.
[0069] The present invention also provides a coating composite, comprising a substrate and a coating coated on the substrate, wherein the raw materials for preparing the coating include resin and filler, and the filler is the defective titanium-based metal organic framework material described in the above technical solution.
[0070] In the present invention, the material of the substrate preferably includes wood.
[0071] In the present invention, the resin is preferably polyurethane.
[0072] The present invention does not specifically limit the amount of filler added to the raw materials for preparing the coating, and those skilled in the art can set it according to actual needs.
[0073] The present invention does not specifically limit the thickness of the coating, and those skilled in the art may set the thickness according to actual needs.
[0074] The preparation method and application of the defective titanium-based metal organic framework material, the method for photocatalytic degradation of formaldehyde and the coating composite provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0075] Example 1
[0076] The preparation method of defective titanium-based metal organic framework material comprises the following steps:
[0077] 0.1g TiO2 (particle size 25nm) was ultrasonically dispersed in a mixed solvent containing 45mL N,N-dimethylformamide and 5mL methanol; then 1.087g 2-aminoterephthalic acid was added until it was completely dissolved. Then acetic acid (the mass of acetic acid was 30% of the mass of 2-aminoterephthalic acid) was added dropwise, and after stirring evenly, 0.52mL Ti(OiPr)4 was added to the above mixed liquid to obtain a reaction raw material liquid. Then the reaction raw material liquid was transferred to a Teflon-lined stainless steel autoclave, heated at 150°C for 24h, cooled to room temperature, and centrifuged at 8000rpm for 5min to obtain a solid product; the obtained solid product was washed 3 times with N,N-dimethylformamide and methanol respectively, and then purified at 80°C for 6h using ethanol and acetic acid (9:1, V / V); then activated at a vacuum degree of 0.08MPa and 150°C for 12h to obtain a precursor. The precursor was treated with argon plasma at a low pressure of 20Pa and a power of 200W for 60min to obtain a defective titanium-based metal-organic framework material named TiO2@NM1.
[0078] Example 2
[0079] The preparation method of defective titanium-based metal organic framework material comprises the following steps:
[0080] 0.1g TiO2 (particle size 25nm) was ultrasonically dispersed in a mixed solvent containing 45mL N,N-dimethylformamide and 5mL methanol; then 1.087g 2-aminoterephthalic acid was added until it was completely dissolved. Then acetic acid (the mass of acetic acid was 60% of the mass of 2-aminoterephthalic acid) was added dropwise, and after stirring evenly, 0.52mL Ti(OiPr)4 was added to the above mixed liquid to obtain a reaction raw material liquid. Then the reaction raw material liquid was transferred to a Teflon-lined stainless steel autoclave and heated at 150℃ for 24h. After cooling to room temperature, it was centrifuged at 8000rpm for 5min to obtain a solid product; the solid product was washed 3 times with N,N-dimethylformamide and methanol respectively, and then purified at 80℃ for 6h using ethanol and acetic acid (9:1, V / V); then activated at a vacuum degree of 0.08MPa and 150℃ for 12h to obtain a precursor. The precursor was treated with argon plasma at a low pressure of 20Pa and a power of 200W for 60min to obtain a defective titanium-based metal-organic framework material named TiO2@NM2.
[0081] Example 3
[0082] The preparation method of defective titanium-based metal organic framework material comprises the following steps:
[0083] 0.1g TiO2 (particle size 25nm) was ultrasonically dispersed in a mixed solvent containing 45mL N,N-dimethylformamide and 5mL methanol, and then 1.087g 2-aminoterephthalic acid was added until it was completely dissolved. Then acetic acid (the mass of acetic acid was 90% of the mass of 2-aminoterephthalic acid) was added dropwise, and after stirring evenly, 0.52mL Ti(OiPr)4 was added to the above mixed liquid to obtain a reaction raw material liquid. Then the reaction raw material liquid was transferred to a Teflon-lined stainless steel autoclave and heated at 150℃ for 24h. After cooling to room temperature, it was centrifuged at 8000rpm for 5min to obtain a solid product; the solid product was washed 3 times with N,N-dimethylformamide and methanol respectively, and then purified at 80℃ for 6h using ethanol and acetic acid (9:1, V / V); then activated at a vacuum degree of 0.08MPa and 150℃ for 12h to obtain a precursor. The precursor was treated with argon plasma at a low pressure of 20Pa and a power of 200W for 60min to obtain a defective titanium-based metal-organic framework material named TiO2@NM3.
[0084] Example 4
[0085] The preparation method of defective titanium-based metal organic framework material comprises the following steps:
[0086] 0.1g TiO2 (particle size 25nm) was ultrasonically dispersed in a mixed solvent containing 45mL N,N-dimethylformamide and 5mL methanol; then 1.087g 2-aminoterephthalic acid was added until it was completely dissolved. Then acetic acid (the mass of acetic acid was 120% of the mass of 2-aminoterephthalic acid) was added dropwise, and after stirring evenly, 0.52mL Ti(OiPr)4 was added to the above mixed liquid to obtain a reaction raw material liquid. Then the reaction raw material liquid was transferred to a Teflon-lined stainless steel autoclave and heated at 150℃ for 24h. After cooling to room temperature, it was centrifuged at 8000rpm for 5min to obtain a solid product; the solid product was washed three times with N,N-dimethylformamide and methanol respectively, and then purified at 80℃ for 6h using ethanol and acetic acid (9:1, V / V); then activated at a vacuum degree of 0.08MPa and 150℃ for 12h to obtain a precursor. The precursor was treated with argon plasma at a low pressure of 20Pa and a power of 200W for 60min to obtain a defective titanium-based metal-organic framework material named TiO2@NM4.
[0087] Example 5
[0088] The preparation method of defective titanium-based metal organic framework material comprises the following steps:
[0089] 0.1g TiO2 (particle size 25nm) was ultrasonically dispersed in a mixed solvent containing 45mL N,N-dimethylformamide and 5mL methanol; then 1.087g 2-aminoterephthalic acid was added until it was completely dissolved. Then acetic acid (the mass of acetic acid was 150% of the mass of 2-aminoterephthalic acid) was added dropwise, and after stirring evenly, 0.52mL Ti(OiPr)4 was added to the above mixed liquid to obtain a reaction raw material liquid. Then the reaction raw material liquid was transferred to a Teflon-lined stainless steel autoclave and heated at 150℃ for 24h. After cooling to room temperature, it was centrifuged at 8000rpm for 5min to obtain a solid product; the obtained solid product was washed 3 times with N,N-dimethylformamide and methanol respectively, and then purified at 80℃ for 6h using ethanol and acetic acid (9:1, V / V); then activated at a vacuum degree of 0.08MPa and 150℃ for 12h to obtain a precursor. The precursor was treated with argon plasma at a low pressure of 20Pa and a power of 200W for 60min to obtain a defective titanium-based metal-organic framework material named TiO2@NM5.
[0090] Comparative Example 1
[0091] The preparation method of defective titanium-based metal organic framework material comprises the following steps:
[0092] 0.1g TiO2 (particle size 25nm) was ultrasonically dispersed in a mixed solvent containing 45mL N,N-dimethylformamide and 5mL methanol. 1.087g 2-aminoterephthalic acid was added until it was completely dissolved. 0.52mL Ti(OiPr)4 was added to the above mixture to obtain a reaction raw material solution. The reaction raw material solution was then transferred to a Teflon-lined stainless steel autoclave and heated at 150°C for 24h. After cooling to room temperature, it was centrifuged at 8000rpm for 5min to obtain a solid product; the solid product was washed three times with N,N-dimethylformamide and methanol respectively, and dried at 80°C for 12h; then activated at a vacuum degree of 0.08MPa and 150°C for 12h to obtain a precursor. The precursor was treated with argon plasma at a low pressure of 20Pa and a power of 200W for 60min to obtain a defective titanium-based metal organic framework material, named TiO2@NM0.
[0093] Comparative Example 2
[0094] The preparation method of defective titanium-based metal organic framework material comprises the following steps:
[0095] 0.1g TiO2 (particle size 25nm) was ultrasonically dispersed in a mixed solvent containing 45mL N,N-dimethylformamide and 5mL methanol. 1.087g 2-aminoterephthalic acid was added until it was completely dissolved. 0.52mL Ti(OiPr)4 was added to the above mixture to obtain a reaction raw material solution. The reaction raw material solution was then transferred to a Teflon-lined stainless steel autoclave and heated at 150°C for 24h. After cooling to room temperature, it was centrifuged at 8000rpm for 5min to obtain a solid product; the solid product was washed three times with N,N-dimethylformamide and methanol respectively, and dried at 80°C for 12h; then activated at a vacuum degree of 0.08MPa and 150°C for 12h to obtain a defective titanium-based metal organic framework material, named TiO2@NM.
[0096] Comparative Example 3
[0097] 1.087g of 2-aminoterephthalic acid was dissolved in a mixed solvent containing 45mL of N,N-dimethylformamide and 5mL of methanol. 0.52mL of Ti(OiPr)4 was added to the mixed solution to obtain a reaction raw material solution. The reaction raw material solution was then transferred to a Teflon-lined stainless steel autoclave and heated at 150°C for 24h. After cooling to room temperature, the solid product was centrifuged at 8000rpm for 5min to obtain a solid product; the solid product was washed three times with N,N-dimethylformamide and methanol respectively, and dried at 80°C for 12h to obtain NH2-MIL-125.
[0098] Performance Testing
[0099] The crystal structures of TiO2, NH2-MIL-125, TiO2@NM and TiO2@NMX were analyzed by XRD. Figure 1 As shown, Figure 1 The X-ray crystal diffraction patterns of the materials obtained in the examples and comparative examples are shown in FIG. Figure 1 It can be seen that the XRD of pure NH2-MIL-125 is comparable to the results reported in previous literature. The characteristic diffraction peaks of NH2-MIL-125 are located at about 6.8°, 9.7°, 11.7°, 16.6°, 17.9° and 19.5° at 2θ, respectively, and are attributed to the (101), (200), (211), (222), (312) and (400) crystal planes, respectively, indicating the successful synthesis of NH2-MIL-125 catalyst. The diffraction peaks of TiO2 and NH2-MIL-125 can be observed in the spectrum of TiO2@NM, indicating that the presence of TiO2 does not inhibit the formation of NH2-MIL-125 during the self-assembly of defective titanium-based metal organic framework materials, and TiO2@NM is successfully synthesized. During the preparation process, 30wt%, 60wt%, 90wt%, 120wt% and 150wt% of acetic acid were added to synthesize the precursor of 2-aminoterephthalic acid, and after auxiliary plasma treatment, the characteristic diffraction peaks in the spectrum of TiO2@NM did not change, indicating that the plasma treatment did not change the crystal structure of the material.
[0100] Figure 2 The scanning electron microscope images of NH2-MIL-125 (a) obtained in Comparative Example 3, TiO2@NM (b) obtained in Comparative Example 2, TiO2@NM4 (c) obtained in Example 4, and TiO2@NM5 (d) obtained in Example 5 are shown in FIG. Figure 2 a in the figure is the typical morphology of NH2-MIL-125, which is disc-shaped and has a very smooth surface. Figure 2 As can be seen in b, the surface of NH2-MIL-125 has highly dispersed TiO2 grains, while the original TiO2@NM presents a flat circular morphology with no pores on the surface. Figure 2 It can be clearly observed in Fig. c that the TiO2@NM4 sample shows uniformly distributed pores and the surface becomes rough after plasma treatment. Subsequently, with the increase of acetic acid content, the porous defects on the surface of TiO2@NM5 increase and the edges become blurred (see Fig. Figure 2 d) in.
[0101] The photocatalytic degradation of formaldehyde was carried out on the materials obtained in the examples and comparative examples. The adsorption and photocatalytic degradation of formaldehyde were measured in a homemade quartz reactor. The wavelength of the 300W xenon lamp was 200nm to 780nm. A fan was fixed around the sample holder to keep the flow system at room temperature. After the HCHO concentration (4.5ppm) stabilized, the lamp was turned on, and 0.05mg of the materials in the examples and comparative examples were exposed to the airflow containing pollutants and reacted at 33°C. The HCHO concentration was measured by a HCHO analyzer (FormaldemeterHTV-M, PPMTechnology).
[0102] The results are as follows Figure 3 and Figure 4 As shown, Figure 3 The photocatalytic degradation curves of the materials obtained in the examples and comparative examples under visible light are: Figure 4 The degradation efficiency of the photocatalytic degradation of formaldehyde for 120 min of the materials obtained in the examples and comparative examples is shown in FIG. Figure 3 and Figure 4 It can be seen that pure NH2-MIL-125 failed to degrade formaldehyde after 120 minutes of photocatalytic degradation. The formaldehyde removal rate of pure TiO2 after 120 minutes of photocatalytic degradation was 47.84%. The formaldehyde removal rate of TiO2@NM after 120 minutes of photocatalytic degradation was 15.84%. After plasma treatment, the formaldehyde removal rate of TiO2@NM0 after 120 minutes of photocatalytic degradation was 20.24%. However, after adding acetic acid and auxiliary plasma treatment, the photocatalytic effect of the obtained material was significantly improved. With the increase of acetic acid content, the photocatalytic degradation efficiency of the material also increased. TiO2@NM4 has the best photocatalytic activity, and the formaldehyde degradation rate reached 95.27% after 120 minutes. However, when the amount of acetic acid added was further increased to 150wt%, its catalytic efficiency dropped to 72.1%. This may be due to the excessively high acetic acid content, which destroyed the structure of the material to a certain extent, resulting in a reduction in the surface active sites of the material and a decrease in the photocatalytic effect.
[0103] The TiO2@NM4 obtained in Example 4 was subjected to a photocatalytic degradation of formaldehyde experiment 10 times. Each photocatalytic degradation of formaldehyde experiment was carried out in a homemade quartz reactor, 0.05 mg of catalyst was added, the light source was a xenon lamp light source, formaldehyde-containing gas (4.5 ppm) was introduced, and the reaction was carried out at 33°C. After each experiment, the catalyst was taken out, dried, and the next cycle was carried out. The degradation efficiency of each photocatalytic degradation of formaldehyde experiment was as follows: Figure 5 As shown. Figure 5 It can be seen that after 10 cycles of use, the degradation rate of HCHO by TiO2@NM4 obtained in Example 4 is still as high as 88.33%, showing excellent photocatalytic stability.
[0104] The coating composite was prepared using the materials obtained in the examples and comparative examples, specifically, a certain amount of the materials were dispersed in a solvent containing ethanol and ultrasonically dispersed. Then, an aqueous polyurethane emulsion was added to the mixture and ultrasonically stirred to form a uniform suspension. Then, the suspension was sprayed on a wooden substrate (Burmese rosewood) at a pressure of 20 to 30 psi, and naturally dried at room temperature to form a coating composite. The spraying distance was 15 cm.
[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a defective titanium-based metal-organic framework material, characterized in that: The following steps are involved: In an organic solvent, titanium dioxide, 2-aminoterephthalic acid, acetic acid and an organic titanium source are sequentially added to obtain a reaction raw material liquid; The reaction raw material liquid is reacted to obtain a precursor; The precursor is subjected to plasma treatment to obtain the defective titanium-based metal organic framework material.
2. The preparation method according to claim 1, characterized in that: The mass of the acetic acid is 30-150% of the mass of 2-aminoterephthalic acid.
3. The preparation method according to claim 1, characterized in that: The dosage ratio of the 2-aminoterephthalic acid and the organic titanium source is 0.8-1.2:0.45-0.52 g / mL; The mass ratio of the titanium dioxide to the organic titanium source is 0.1:1 to 0.2:1, and the particle size of the titanium dioxide is 20 to 25 nm; The organic titanium source includes tetraisopropyl titanate.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The reaction temperature is 120-160° C. and the reaction time is 20-26 hours.
5. The preparation method according to claim 1, characterized in that: After the reaction, the method further comprises: centrifuging the obtained reaction liquid, washing, purifying and vacuum activating the obtained solid in sequence to obtain a precursor; The centrifugal separation is performed at a speed of 8000 to 10000 rpm for 5 to 10 minutes; The washing comprises sequentially performing N,N-dimethylformamide washing and methanol washing; the number of N,N-dimethylformamide washing is ≥3 times, and the number of methanol washing is ≥3 times; The purification reagent includes ethanol and acetic acid, the volume ratio of ethanol to acetic acid is 9:1, the purification temperature is 80-90°C, and the time is 5-7h; The vacuum degree of the vacuum activation is 0.05MPa-0.09MPa, the temperature is 120-150°C, and the time is 10-24h.
6. The preparation method according to claim 1, characterized in that: The plasma treatment is argon plasma treatment, the pressure of the argon plasma treatment is 20 Pa, the power is 100-300 W, and the time is 40-120 min.
7. The defective titanium-based metal organic framework material obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the defective titanium-based metal organic framework material according to claim 7 in photocatalytic degradation of formaldehyde.
9. A method for photocatalytic degradation of formaldehyde, characterized in that: The following steps are involved: The catalyst is brought into contact with the formaldehyde-containing gas, and the formaldehyde is degraded under light conditions; The catalyst is the defective titanium-based metal organic framework material as described in claim 7.
10. A coating composite, characterized in that: It comprises a substrate and a coating coated on the substrate, wherein the raw materials for preparing the coating comprise resin and filler, and the filler is the defective titanium-based metal organic framework material as claimed in claim 7.
Citation Information
Cited By
Activated carbon fiber capable of efficiently removing formaldehyde and preparation method of activated carbon fiber
CN120575362A